THERAPEUTIC EFFICACY OF NANO BERBERINE GEL VERSUS 1% SILVER SULFADIAZINE IN PEDIATRIC THERMAL BURN INJURIES (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the clinical efficacy, bacterial control ability, and the molecular mechanisms underlying the wound healing effects of Berberin nano gel compared with Silver Sulfadiazine 1% cream (SSD 1%) on superficial thermal burns in pediatric patients.Methods: A prospective, controlled, within-patient (split-wound) study in 34 children with II-III degree burns treated at Le Huu Trac National Burn Hospital. Each child had two damaged zones that were equivalent: Zone A was treated with Berberine nano gel, and Zone B was treated with SSD 1%. Evaluation of complete healing time, time to 50% epithelialization, surface bacterial load (D0, D7, D14), and CHEOPS pain score.Results: Time to complete healing was shortened with Berberine nano gel: superficial second-degree 8.26 ± 2.45 days vs. 9.71 ± 2.95 days; third-degree 14.85 ± 5.20 days vs. 18.41 ± 6.56 days (p
Keywords: Nano Berberine; Superficial burns in children; Antibacterial.